Development of graphene oxide-modified bismuth oxide nanomaterials for electrochemical and light-activated catalytic applications - Amika; Deepak Kumar; Dinesh Kumar; Azad Qayoom Malik; Bhawna; Nabisab Mujawar Mubarak; Mohamed Aly Saad Aly (Environmental Nanotechnology, Monitoring & Management, 2026)

A culture-based protocol for isolation and preliminary antibiotic susceptibility screening of soil bacteria - Sapna Kumari; Zeba Anjum; Diva Kumar Manglam; Sujata Kumari; Gajendra Kumar Azad (Next Research, 2026)

Machine learning based optimization of polyhydroxybutyrate (PHB) production from Gordonia amicalis NSPS90 and elucidation of PHB biosynthesis genes, their pathways through gene network analysis - Guddu Kumar Gupta; Eetika Chot; Danyang Shao; Nitu Shah; Anjali Topno; Rajeev K. Azad; Pratyoosh Shukla (Bioresource Technology Reports, 2026)

Changing patterns of meteorological droughts across the northern part of Bangladesh using RAI and SPI-based indices - Md Abrarul Hoque; Sajal Kumar Adhikary; Abdullah All Noman; Rubinoor Islam; Md. Abul Kalam Azad; Md. Zakir Hossain; Md. Iftakhar-Ul Islam (Theoretical and Applied Climatology, 2026)

Retraction Note: A deletion mutant ndv200 of the Bacillus thuringiensis vip3BR insecticidal toxin gene is a prospective candidate for the next generation of genetically modified crop plants resistant to lepidopteran insect damage - Srimonta Gayen; Milan Kumar Samanta; Munshi Azad Hossain; Chandi Charan Mandal; Soumitra Kumar Sen (Planta, 2026)

Sorption and subsequent photodegradation of crystal violet dye by CdS and Cu@CdS prepared using Desulfovibrio vulgaris AU16 - Shivesh Kumar Azad; Maulin P. Shah; Manoj Kumar Gangwar; Prashant D. Kunjadia; Madhu Kumari; Fuad Ameen; Kumar Suranjit Prasad (Journal of Water Process Engineering, 2026)

Sustainable aquaculture: An Iot-integrated system for real-time water quality monitoring featuring advanced do and ammonia sensors - Abrar Zuhaer; Azad Khandoker; Nafees Enayet; Pronab Kumar Paul Partha; Md. Abdul Awal (Aquacultural Engineering, 2026)

Improved GA-ANN based optimized bio-deinking strategy for laccase produced from Trametes versicolor GGRK18, and its gene co-expression network analysis - Guddu Kumar Gupta; Tallon Coxe; Eetika Chot; Rajeev Kumar Kapoor; Deepak Chhabra; Nishi Kant Bhardwaj; Rajeev K. Azad; Pratyoosh Shukla (Journal of Environmental Chemical Engineering, 2025)

Influence of metal ions on the economic parameters of mulberry silkworm Bombyx mori (Lepidoptera: Bombycidae) - Azad Gull; Mysore Nagaraj Anil Kumar; Amit Kumar (Biologia Futura, 2025)

Assessment and prediction of forest structural attributes in tropical deciduous forests - Pavan Kumar; Prem Chandra Pandey; Azad Rasul; Ramesh K. Ningthoujam (International Journal of Remote Sensing, 2025)

Evaluating landuse and climate change effects on current and future hydrologic response and its economic valuation in a North-Indian basin using SWAT - Meraj Alam Ansari; Natesan Ravisankar; Himanshu Joshi; Meenu Rani; Mohammad Shamim; Adlul Islam; Ashisa K. Prusty; Raghavendra K. J.; Raghuveer Singh; Sunil Kumar; Azad S. Panwar (Sustainable Water Resources Management, 2025)

Nanomaterials via ZIF-8: Preparations, catalytic and drug delivery applications - Kumkum Priyadarshini Sahu; Suryabhan Singh; Ashish Kumar Singh; Uday Pratap Azad; Dibya Yadav; Vinod Kumar; Sunil Kumar Singh (Chemical Engineering Journal, 2025)

Identification of terminal heat-tolerant and foliar disease-resistant fortified genotypes in wheat (Triticum aestivum L.) - Rounak Kumar; Chandra Shekhar Azad; Tirthartha Chattopadhyay; Pradeep Kumar Bhati; Om Prakash Gangwar; Subodh Kumar; Pramod Prasad; Deepak Baranwal (Cereal Research Communications, 2024)

Molecularly imprinted Ag2S quantum dots with high photocatalytic activity for dye removal: Experimental and DFT insights - Azad Quyoom Malik; Tabinda Jabeen; Prasad Eknath Lokhande; Deepak Kumar; Shikha Awasthi; Sarvesh Kumar Pandey; Nabisab Mujawar Mubarak; Faisal Abnisa (Journal of Environmental Management, 2024)

Retraction Note: EGFR Targeted Paclitaxel and Piperine Co-loaded Liposomes for the Treatment of Triple Negative Breast Cancer - Ankita Sanjay Burande; Matte Kasi Viswanadh; Abhishek Jha; Abhishesh Kumar Mehata; Azad Shaik; Nishi Agrawal; Suruchi Poddar; Sanjeev Kumar Mahto; Madaswamy S. Muthu (AAPS PharmSciTech, 2024)

Biochemical analysis of defensive enzymes in the hemolymph of bivoltine silkworm breeds of Bombyx mori (Lepidoptera: Bombycidae) - Ravindra Mahadappa Aurade; Azad Gull; Dhaneshwar Padhan; Nalavadi Chandrakanth; Harish Kumar Jayaram; Keerthana Satish; Shunmugam Manthira Moorthy; Subramaniam Gandhi Doss (Biologia, 2024)

Alleviation of arsenic-induced neurobehavioral defects with selenium in the larvae of Zaprionus indianus - Shilpi Kumari; Puja Kumari; Sneha Sinha; Gajendra Kumar Azad; Shahla Yasmin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Histone H3 N-terminal tail provides tolerance to tartrazine induced stress in Saccharomyces cerevisiae - Smriti Anand; Sushant Kumar; Khushboo Kumari; Gajendra Kumar Azad (Biologia, 2024)

Navigating Sustainability through Greenhouse Gas Emission Inventory: ESG Practices and Energy Shift in Bangladesh’s Textile and Readymade Garment Industries - Mithun Kumar Biswas; Abul Kalam Azad; Anupa Datta; Shuvasish Dutta; Shimul Roy; Shauhrat S. Chopra (Environmental Pollution, 2024)

Facile Synthesis of S-doped Carbon Quantum Dots and Their Application in the Detection of Sudan I in Saffron - Tahir ul Gani Mir; Azad Qayoom Malik; Saurabh Shukla; Jaskaran Singh; Deepak Kumar (Journal of Fluorescence, 2024)

A critical review and future perspective of plastic waste recycling - Rahul Tiwari; Numanuddin Azad; Deblina Dutta; Bholu Ram Yadav; Sunil Kumar (Science of The Total Environment, 2023)

A review on the green synthesis of nanoparticles, their biological applications, and photocatalytic efficiency against environmental toxins - Azad Qayoom Malik; Tahir ul Gani Mir; Deepak Kumar; Irtiqa Ashraf Mir; Adfar Rashid; Mehnaz Ayoub; Saurabh Shukla (Environmental Science and Pollution Research, 2023)

Synergy of silica sand and waste plastics as thermoplastic composites on abrasive wear characteristics under conditions of different loads and sliding speeds - Ashish Soni; Pankaj Kumar Das; Mohammad Yusuf; Syahrir Ridha; Hesam Kamyab; Mohammad Azad Alam; Faisal Masood; Shreeshivadasan Chelliapan; Mohd Ubaidullah; Bidhan Pandit; Chander Prakash (Chemosphere, 2023)

Multisectoral prioritization of zoonotic diseases in Haryana (India) using one health approach - Hanul Thukral; K. Shanmugasundaram; T. Riyesh; Naveen Kumar; Harisankar Singha; Dolly Gambhir; Azad Laura; Simmi Tiwari; Baldev R. Gulati (Preventive Veterinary Medicine, 2023)

Arsenite and arsenate ions adsorption onto a biogenic nano-iron entrapped dual network Fe@alginate-κ-carrageenan hydrogel beads - Anushree Srivastava; Shivesh Kumar Azad; Kavita Singh; Bablu Prasad; Madhu Kumari; Nandan; Amresh Kumar Sahoo; Hemen Dave; Deepak M. Maurya; Deepak Singh; Kumar Suranjit Prasad (Nanotechnology for Environmental Engineering, 2023)

Wastewater generation and treatment by various eco-friendly technologies: Possible health hazards and further reuse for environmental safety - Bhanu Pratap; Saroj Kumar; Sampurna Nand; Iqbal Azad; Ram Naresh Bharagava; Luiz Fernando Romanholo Ferreira; Venkatesh Dutta (Chemosphere, 2023)

Synthesis of TiO2, TiO2/PAni, TiO2/PAni/GO nanocomposites and photodegradation of anionic dyes Rose Bengal and thymol blue in visible light - Azad Kumar; Chaitany Jayprakash Raorane; Asad Syed; Ali H. Bahkali; Abdallah M. Elgorban; Vinit Raj; Seong Cheol Kim (Environmental Research, 2023)

Toxicity profile of Phaleria macrocarpa (Scheff.) Boerl. fruits extract in adult male Sprague-Dawley rats - Abul Kalam Azad; Wan Mohd Azizi Wan Sulaiman; Sukalyan Kumar Kundu (Advances in Traditional Medicine, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Geotechnical and geological studies of Adit-6 of the railway tunnel between Rishikesh and Karnprayag in India focusing on the excavation methods and design of support analysis: a case study - Md Alquamar Azad; Somendra Kumar Singh; Apurva Alok; Meenakshi; Saurav Shekhar; Prem Kumar (Arabian Journal of Geosciences, 2022)

Differential response of the nitrifying microbes and net nitrification rates (NNRs) between different cereal and legume crop soils with chemical fertilization - Moumita Sintia; M. Mizanur Rahman; Azmerry Khanom; Md. Amdadul Huq; Md. Yousof Ali; Mamoona Rauf; Nilufa Ahkter Banu; Sudhangshu Kumar Biswas; Md. Abul Kalam Azad (Arabian Journal of Geosciences, 2021)

Influence of the water–sediment interaction on the major ions chemistry and fluoride pollution in groundwater of the Older Alluvial Plains of Delhi, India - Shakir Ali; Shashank Shekhar; Trupti Chandrasekhar; Akhilesh Kumar Yadav; Naresh Kumar Arora; Chandrashekhar Azad Kashyap; Prosun Bhattacharya; S P Rai; Prabhas Pande; Dornadulla Chandrasekharam (Journal of Earth System Science, 2021)

COVID-19 Creating another problem? Sustainable solution for PPE disposal through LCA approach - Harender Kumar; Amaanuddin Azad; Ankit Gupta; Jitendra Sharma; Hemant Bherwani; Nitin Kumar Labhsetwar; Rakesh Kumar (Environment, Development and Sustainability, 2021)

Correction to: EGFR Targeted Paclitaxel and Piperine Co-loaded Liposomes for the Treatment of Triple Negative Breast Cancer - Ankita Sanjay Burande; Matte Kasi Viswanadh; Abhishek Jha; Abhishesh Kumar Mehata; Azad Shaik; Nishi Agrawal; Suruchi Poddar; Sanjeev Kumar Mahto; Madaswamy S. Muthu (AAPS PharmSciTech, 2020)

Spatiotemporal mapping mangroves of Tengragiri wildlife sanctuary under Barguna district of Bangladesh using freely available satellite imagery - Md. Mozahidul Islam; Ruhul Mohaiman Chowdhury; A. K. M. Mostafa Zaman; Md. Saifur Rahman; Md. Nazrul Islam; Ajit Kumar Rudra; Md. Salim Azad (Modeling Earth Systems and Environment, 2020)

Effect of Long-Term Pesticides and Chemical Fertilizers Application on the Microbial Community Specifically Anammox and Denitrifying Bacteria in Rice Field Soil of Jhenaidah and Kushtia District, Bangladesh - M. Mizanur Rahman; Kamrun Nahar; Md. Meraj Ali; Nasrin Sultana; Mohammad Minnatul Karim; Utpal Kumar Adhikari; Mamoona Rauf; Md. Abul Kalam Azad (Bulletin of Environmental Contamination and Toxicology, 2020)

RETRACTED ARTICLE: EGFR Targeted Paclitaxel and Piperine Co-loaded Liposomes for the Treatment of Triple Negative Breast Cancer - Ankita Sanjay Burande; Matte Kasi Viswanadh; Abhishek Jha; Abhishesh Kumar Mehata; Azad Shaik; Nishi Agrawal; Suruchi Poddar; Sanjeev Kumar Mahto; Madaswamy S. Muthu (AAPS PharmSciTech, 2020)

RETRACTED ARTICLE: A deletion mutant ndv200 of the Bacillus thuringiensis vip3BR insecticidal toxin gene is a prospective candidate for the next generation of genetically modified crop plants resistant to lepidopteran insect damage - Srimonta Gayen; Milan Kumar Samanta; Munshi Azad Hossain; Chandi Charan Mandal; Soumitra Kumar Sen (Planta, 2015)

Ebselen, a promising antioxidant drug: mechanisms of action and targets of biological pathways - Gajendra Kumar Azad; Raghuvir S. Tomar (Molecular Biology Reports, 2014)

Proteolytic clipping of histone tails: the emerging role of histone proteases in regulation of various biological processes - Gajendra Kumar Azad; Raghuvir S. Tomar (Molecular Biology Reports, 2014)

Variant cry1Ab entomocidal Bacillus thuringiensis toxin gene facilitates the recovery of an increased number of lepidopteran insect resistant independent rice transformants against yellow stem borer (Scirpophaga incertulus) inflicted damage - Abhijit Dandapat; Jagannath Bhattacharyya; Srimonta Gayen; Anirban Chakraborty; Anannya Banga; Rajeswari Mukherjee; Chandi Charan Mandal; Munshi Azad Hossain; Samarjit Roy; Asitava Basu; Soumitra Kumar Sen (Journal of Plant Biochemistry and Biotechnology, 2014)

Erratum to: Metabolic responses of tea (Camellia sp.) to exogenous application of ascorbic acid - Amarchand Chordia Murugan; Jibu Thomas; Raj Kumar Rajagopal; Abul Kalam Azad Mandal (Journal of Crop Science and Biotechnology, 2012)

Wound healing activity of carbon monoxide liberated from CO-releasing molecule (CO-RM) - Azad Ahmad Ahanger; Shahid Prawez; Dhirendra Kumar; Raju Prasad; Amarpal; Surendra Kumar Tandan; Dinesh Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Pseudomonas aeruginosa inducing rice resistance againstRhizoctonia solani: Production of salicylic acid and peroxidases - R. Saikia; R. Kumar; D. K. Arora; D. K. Gogoi; P. Azad (Folia Microbiologica, 2006)